Analisis Sistem Kerja dalam Meningkatkan Kinerja Tenaga Kependidikan melalui Employee Engagement menggunakan Structural Equation Modeling - Galih Adi Rustanto; Siti Muhimatul Khoiroh (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study uses structural equation modelling (SEM) to examine how work systems affect employee performance among educational support personnel at a public university in Surabaya, with employee engagement acting as a mediating variable. Data were collected from 293 respondents using a Likert-scale questionnaire. The results show that the work system has a significant positive effect on employee engagement (β = 0.541; CR = 6.840), employee engagement has a significant positive effect on employee performance (β = 0.253; CR = 4.168), and the work system has a direct effect on employee performance (β = 0.341; CR = 4.991). The Sobel Test yielded Z = 3.55 (> 1.96), demonstrating that the relationship between the work system and performance is substantially mediated by employee involvement, confirming partial mediation. The findings underscore the importance of improving work systems encompassing physical, technological, and cultural environments as a strategy for enhancing engagement and performance among educational support staff.